THE FORMATION OF SKILLS IN THE TRANSMISSION OF HUMAN MOVEMENT IN SCULPTURE IN GENERAL EDUCATION ESTABLISHMENTS - Elizaveta Maksimovna Semenova (Science and Innovation Center Publishing House, 2019)
The article is devoted to finding of the optimum training methodology оf the Human movement representation in sculpture classes in general education establishments. The study determines the fundamental foundations of training and a series of exercises aimed at learning special skills.